ALARM INDICATOR ANALYSIS ON CORE SUBSYSTEM FOR ENHANCES RELIABILITY AND AVAILABILITY IN AERONAUTICAL MESSAGE HANDLING SYSTEM - Prasojo, Muhamad Adimukti; Wildan, Muh; Eriyandi, Eriyandi (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
Perum LPPNPI Palembang uses the AMHS Comsoft brand, which has a Core Subsystem (CSS), a module used to connect with external communication partners, handle different protocols, and receive store and forward messages. This research aims to analyze the alarm indicators on CSS A by performing corrective maintenance, which consists of inspection, equipment troubleshooting, and problem-solving. This research uses a descriptive qualitative method by collecting data from observation and document analysis to explore the relationship in each context. The inspection results found a way to restore the alarm using corrective maintenance such as checking the condition or inspecting the equipment, troubleshooting by conducting connectivity checking and performing problem-solving by routing the address. By conducting this research, AMHS equipment can operate using 2 CSS modules (CSS A and CSS B) so that CSS can operate redundantly. One CSS is in operational mode, and the second CSS waits in a hot standby mode, so it impacts optimal performance, reduces downtime, and enhances operational reliability and availability for aviation communication systems to enhance aviation safety standards.